The impact of parenthood on the gender wage gap: A comparative analysis of 26 European countries - Ewa Cukrowska-Torzewska; Anna Lovász (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2017)
We use cross-national data on 26 EU countries to assess how much children and the responsibilities related to them contribute to the gender wage gap, and how institutional elements - especially family policies - affect this relationship. Our analysis is based on a decomposition that reveals what portion of the gender wage gap may be attributed to: (1) the motherhood wage penalty, (2) the fatherhood wage premium, and (3) the gender wage gap among childless individuals. Our findings suggest that the variability in the magnitude of the gaps is closely related to the institutional context, pointing to different reasons behind the gender wage gap and policy implications. Southern EU countries have low gender wage gaps and low motherhood penalties or even premiums. Short leaves, low childcare coverage, and traditional norms do not support maternal labor supply, but mothers who work do not face a wage penalty. Western EU countries with higher childcare coverage, moderate length leaves, supportive norms, and flexible jobs have relatively high maternal employment and mothers are not faced with significant wage penalties. The highest motherhood penalties are found in CEE countries, where long leaves, low childcare availability under age 3, and preferences for within-family care lead to long absences from the labor market. In all countries, irrespective of cultural norms and policies, we find high positive family gaps among men, which drive men's average wages up, and lead to gender wage inequality.
Keywords: J13; J22; 330; Family Gap; Gender Wage Gap; Family Policies